(3GdEbJUGO GdQjGVj (B:s (3eMGVQGJ hJeGQjf eMdhdI (B/s - (3RZjH, TgQRGOs; (3Hf OjH, QTjOs ((3GdLRGFQ(B: s (3OjhGf GdeWHhYGJ GdLGeYjI(B, s, 2014)
(3JfGhd gPG GdcJGH GdGbJUGO GdQjGVj hHjf ef NdGd aUhdg GdbhGYO GdLHQjI hGdNWjI hJWHjbGJgG GdGbJUGOjI GdJj LSOJ ef LgI aj GdJMdjd hLgI CNQi aj JeGQjf eMdhdI , HGdEVGaI Gdi JhVjMGJ ddeaGgje GdCSGSjI hGdVQhQjI GdeJYdbI HTcd YGe HGdeJZjQGJ hGdYdGbGJ GdGbJUGOjI (B. s
(3GdeQGLY U(B.365 (3bGFeI GdeUWdMGJ U(B.357s
Keywords: (3GdGbJUGO GdQjGVjs